Consumer's perception and acceptance towards Facebook advertising / Joanna Badong Gilbert - Gilbert, Joanna Badong (2015)
Understanding consumer’s attitudes toward advertising has always been one of the goals of advertisers. Advertisements that are successful in delivering its messages to its audiences can help to promote and build awareness on the company’s offerings. With the rapid development of information technologies worldwide in the past decade, advertisers are increasingly relying on various modes of interactive technology to advertise and promote their products and services. Furthermore, the idea of executing a content that is current and entertaining could get consumers to interact electronically in an effective way. This powerful attribute can be seen as a future of advertising and may become more figurative in consumers’ minds than television advertising as a marketing stimulus that stands out relative to others in the environment Yaakop, A and Hemsly Brown, J. (2001).